The Relationship Between Family Socio-Economic Factors and the Incidence of Stunting in Children Aged 0-5 Years) in the Working Area of Pitu Public Health Center - Olivia Asih Blandina; Fanda Volatris Majiko; Yurensi Felni Tjingaisa (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Stunting is a growth disorder in children caused by chronic malnutrition that occurs over a long period, especially during the first 1,000 days of life. Several factors contribute to stunting, including environmental, cultural, healthcare services, inadequate maternal nutrition during pregnancy, and socioeconomic conditions. North Maluku Province shows a concerning rate of 27.5%. This study aims to determine the relationship between family socioeconomic factors and the incidence of stunting among children aged 0–5 years in the working area of Pitu Public Health Center. This research employed a quantitative method with a cross-sectional approach. The population consisted of 61 families with stunted children, and 53 respondents were selected as samples using a purposive sampling technique. Data were collected using questionnaires and analyzed univariately and bivariately with the Spearman’s rho test. The results showed that most respondents had a moderate socioeconomic level (37.7%), followed by high (34.0%) and low (28.3%). The highest incidence of stunting was found in the moderate category at 39.6%. The correlation test indicated a significance value of 0.598 (p > 0.05), which means there was no significant relationship between family socioeconomic factors and stunting incidence. These findings indicate that stunting can occur even when family economic conditions are relatively good. Therefore, stunting prevention requires a holistic approach through nutrition education, improved parenting practices, promotion of clean and healthy living behaviors, regular monitoring of child growth and development, and continuous support from healthcare workers and community health post cadres.